Power, Suffering, and the Struggle for Dignity : Human Rights Frameworks for Health and Why They Matter - Yamin, Alicia Ely (Book collections on Project MUSE., 2016)
Directed at a diverse audience of students, legal and public health practitioners, and anyone interested in understanding what human rights-based approaches (HRBAs) to health and development mean and why they matter, Power, Suffering, and the Struggle for Dignity provides a solid foundation for comprehending what a human rights framework implies and the potential for social transformation it entails. Applying a human rights framework to health demands that we think about our own suffering and that of others, as well as the fundamental causes of that suffering. What is our agency as human subjects with rights and dignity, and what prevents us from acting in certain circumstances? What roles are played by others in decisions that affect our health? How do we determine whether what we may see as "natural" is actually the result of mutable, human policies and practices? Alicia Ely Yamin couples theory with personal examples of HRBAs at work and shows the impact they have had on people's lives and health outcomes. Analyzing the successes of and challenges to using human rights frameworks for health, Yamin charts what can be learned from these experiences, from conceptualization to implementation, setting out explicit assumptions about how we can create social transformation. The ultimate concern of Power, Suffering, and the Struggle for Dignity is to promote movement from analysis to action, so that we can begin to use human rights frameworks to effect meaningful social change in global health, and beyond.